Scent upon a Southern Breeze : The Synaesthetic Arts of the Deccan (Marg Publications, 2018)
The arts of the Deccan remained understudied for a long while, possibly due to their complex and hybrid nature. This was a coveted region, and many powers fought over its control. What survives of its turbulent history allows us to reconstruct only a fragmentary record of what might have been made in the Deccan. Even in what remains, it is not always easy to put one$1 (Bs finger on what is "Deccani" in Deccani art. Now, in the wake of global art history and its interest in travelling objects and hybridity, Deccani art is increasingly coming into focus. Scholars are bringing new insights to Deccani objects that bear the marks of mixed styles, trade, and even damage and reconstitution. Drawing from and going beyond the landmark 2015 symposium and exhibition Nauras: The Many Arts of the Deccan held at the National Museum, New Delhi, the essays in this volume explore the sense of wonder, 'aja'ib, that permeated textile design, manuscript illustration and perfume production in the Deccan. Through Ragamala paintings and treatises on magic, perfumery texts and garden architecture, exquisite bidri ware and kalamkaris, the volume shows the way objects and texts can yield an understanding of how beauty was experienced in the past not just through visual means but through sound and smell as well. The book breaks new ground for a sensory turn in Indian art history. Visual objects become crucibles for synaesthetic experiences, as we look upon them with new eyes, or with more than eyes. Kavita Singh is Professor and currently Dean at the School of Arts and Aesthetics, Jawaharlal Nehru University, New Delhi, where she teaches courses on the history of Indian painting and the history and politics of museums.s
English
Keywords: N4390-5098 Visual Arts- Exhibitions; India